Cardiovascular and renal safety of metformin in patients with diabetes and moderate or severe chronic kidney disease: Observations from the EXSCEL and SAVOR‐TIMI 53 cardiovascular outcomes trials. Issue 5 (2nd February 2021) - Clegg, Lindsay E.; Jing, Yankang; Penland, Robert C.; Boulton, David W.; Hernandez, Adrian F.; Holman, Rury R.; Vora, Jiten
Abstract: Aim: To provide evidence on the cardiovascular and renal safety of metformin in chronic kidney disease (CKD) stages 3 to 4. Materials and Methods: This post hoc analysis compared participants with an estimated glomerular filtration rate (eGFR) of 15 to 59 mL/min/1.73m 2 in the Exenatide Study of Cardiovascular Event Lowering (EXSCEL) and the Saxagliptin and Cardiovascular Outcomes in Patients With Type 2 Diabetes Mellitus (SAVOR‐TIMI 53) trials taking metformin, with those not exposed to metformin during these trials, using a propensity‐matching approach. Adjusted Cox proportional hazards models were used to assess risk of major adverse cardiovascular events (MACE) and all‐cause mortality (ACM). Metformin effect on eGFR slope was calculated using a mixed‐model repeated measures analysis, and the number of lactic acidosis events was tabulated. Results: No strong trend for lower metformin doses with lower eGFR values was observed in either the EXSCEL or SAVOR‐TIMI 53 trials. In the 1745 metformin‐using participants matched to non‐metformin users, metformin had neutral effects on MACE (hazard ratio [HR] 0.91, 95% confidence interval [CI] 0.76–1.08; P = 0.28) and ACM (HR 0.86, 95% CI 0.70–1.07; P = 0.18), with no interaction by CKD stage, or with use of exenatide or saxagliptin. An improvement in eGFR slope was observed with metformin in the CKD stage 3B cohort in SAVOR‐TIMI 53, but not in other groups. Conclusions: This analysis of participants with CKD stages 3 to 4 from two cardiovascular outcomes trials supports the cardiorenal safety of metformin, but does not suggest a consistent benefit on MACE, ACM, or eGFR slope across this population.